Taalangst in het klaslokaal: De taalangstniveaus van Hongaarse studenten Neerlandistiek - Gőcze, Borbála (FILOGI, 2022)
The goal of this study was to examine the language anxiety levels of Dutch majors studying at three Hungarian universities (University of Debrecen, Eötvös Loránd University, Károli Gáspár University of the Reformed Church). A questionnaire was distributed to assess the differences between the anxiety levels of bachelor’s and master’s students majoring in Dutch, each section of questions targeting a different area of language learning (input, output, and processing). The results of the questionnaire revealed that the bachelor’s students demonstrate higher levels of anxiety than the master’s students, especially the first-year bachelor’s students. This suggests that the level of fluency may have an influence on the level of anxiety experienced by the students.